HUBUNGAN HASIL TANGKAPAN RAJUNGAN (Portunus pelagicus, Linnaeus 1758) DENGAN KONDISI HIDRO-OSEANOGRAFI DI PERAIRAN KABUPATEN TULANG BAWANG, PROVINSI LAMPUNG - Anma Hari Kusuma; Qadar Hasani; Aris Budiarto; Hari Priyadi; Khairul Amri; Asep Ma’mun; Efri Wahyuni (Universitas Mataram, 2024)
Blue swimming crab is one of the important fishery commodities in Indonesia after shrimp, tuna and macro algae cannot be separated from the condition of the hydro-oceanographic parameters of the waters. The aim of the study was to analyze the relationship between crab catches and hydro-oceanographic conditions. This research was conducted from June to December 2022. The research location was in the waters of the Tulang Bawang Regency, Lampung Province. The highest number of crab catches and fishing fleets was in the West Season while the lowest was in the Second Transitional Season. In the West Season the current speed is 0,45-0,7 m/s, waves range from 0,1-1,25 m, temperature ranges from 28-29°C, salinity ranges from 28-29 ppt and chlorophyll concentration ranges from 0,5- 3,5 mg/m³ while in Transition Season II the current speed ranges from 0,40-0,50 m/s, wave height 0,5-1,25 m, temperature ranges from 29-30,5°C, salinity ranges from 31-22 ppt and chlorophyll concentrations ranged from 0-0,5 mg/m³. There are differences in seasonal variations in crab abundance due to differences in the hydro-oceanographic conditions of the waters which are influenced by the monsoon system. Keywords: Blue Swimming Crab, Hiydro-Oceanopraphy, Tulang Bawang Regency